VEGETABLE PRODUCTION AND THE KNOWLEDGE CONSTRUCTION: AN EXPERIENCE ON SEED ANALYSIS AND TECHNOLOGY - MIGUEL, Marilis Dallarmi (Scientia Agraria, 2001)
The purpose of this work is to evaluate a teaching pedagogic proposal for the agronomic course of UFPR. Using a social critical progressist methodology, it is lntended to make the agronomic students aware of acting as social changing agents. conscious of their historic reality. lt focuses on making the teaching methods feasible under the constructive optical. The research worked with the everyday of the discipline of seed technology and analysis, where it created strategies to broach the matter refered, to promote the development of students on a logic, creative, critical, citizen sense, on behalf of the construction of knowledge. lt lavours the collective and individual work and a series of strategies under a direct interaction with the real performance of the agronomic engineering professional. To valuate the students, 28 multiple choice questions and 11 open questions were employed beyond those questions, they observed the accomplishment of the stages they came through. The main goal of this work was to stimulate the reflexive, conscious and ethnic formation. This procedure made possible to change the agronomic engineering formation. This pedagogics planning were requested, which should be made by a competent professor. This professor has to dominate this area of knowledge and to be a good researcher to promote the progress. He has to be open to discuss and dominate de pedagogic practices and exercise the acting as professor of agronomic engineering, not the contrary.